Heat Transfer Optimization in Laminar Flow of Non-Linear Viscoelastic Fluids in Asymmetric Straight Ducts with Inclusions - Letelier-Sotomayor, M; Gonzalez-Andres, A; Siginer, D (American Society of Mechanical Engineers, 2017)
This paper presents the preliminary findings of an optimization study of transversal flow strength in tube crosssections with arbitrary external contours and an internal inclusion. The eccentric tube contours are generated through a one-to-one mapping of a base circular cross-section. The working fluid obeys the non-linear modified Phan-Thien- Tanner (MPTT) constitutive model. The computation of the total transversal flow rate leads to the determination of effective cross-sections for heat transfer enhancement. Copyright © 2017 ASME.